Motif dan Pola Komunikasi dalam Keputusan Living Together Pada Mahasiswa di Yogyakarta - Risvi Khairil Anam Ahmad (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The phenomenon of living together among university students reflects a shift in how individuals construct and interpret interpersonal relationships. This practice is not merely associated with physical proximity but also involves complex communication dynamics within romantic relationships. Based on a descriptive qualitative approach using in-depth interviews, the findings indicate that the decision to cohabit is shaped by a combination of emotional, practical, and social factors. Communication emerges as a key element in establishing mutual understanding, although initial interactions tend to be implicit and not fully explored. In everyday life, communication becomes more intensive and open, yet it also increases the potential for conflict, requiring management through openness, trust, and negotiation. Social pressure from the surrounding environment is addressed through adaptive strategies, such as limiting external disclosure and strengthening internal communication. These findings suggest that living together functions as a dynamic space for interpersonal communication negotiation in maintaining relationships.